2004
DOI: 10.1097/01.psy.0000127690.38525.ab
|View full text |Cite
|
Sign up to set email alerts
|

Historical Sexual Abuse and Current Thyroid Axis Profiles in Women With Premenstrual Dysphoric Disorder

Abstract: These results suggest increased conversion of T4 to T3 and increased binding of thyroid hormones in women with PMDD with previous sexual abuse. Abnormal total T3 concentrations may have pathophysiological significance in PMDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
5
16
1
Order By: Relevance
“…These observations resulted in our hypothesis that the influence of menstrual cycle on HRV may be related to cyclic variations of thyroid-related hormone levels. Nevertheless, in contrast to previous observations (5,22,53), we failed to identify any significant difference in thyroid-related hormone levels (free T 3 , free T 4 , and TSH) between the follicular phase and luteal phase, as was reported by others (21,29). This finding seems to be contradictory to the evidence that suggested that menstrual cycle physiology may impact hypothalamic-pituitary-thyroid axis function (16,21).…”
Section: Correlations Between Nonlinear and Linear Hrv Measurescontrasting
confidence: 86%
See 2 more Smart Citations
“…These observations resulted in our hypothesis that the influence of menstrual cycle on HRV may be related to cyclic variations of thyroid-related hormone levels. Nevertheless, in contrast to previous observations (5,22,53), we failed to identify any significant difference in thyroid-related hormone levels (free T 3 , free T 4 , and TSH) between the follicular phase and luteal phase, as was reported by others (21,29). This finding seems to be contradictory to the evidence that suggested that menstrual cycle physiology may impact hypothalamic-pituitary-thyroid axis function (16,21).…”
Section: Correlations Between Nonlinear and Linear Hrv Measurescontrasting
confidence: 86%
“…Symptoms arising from "overactivity" or "underactivity" of the thyroid gland resemble sympathovagal unbalance-mediated symptoms (32). Serum thyroglobulin, thyroid volume, and especially thyroid-related hormone levels may vary during the menstrual cycle (5,22,53). These observations resulted in our hypothesis that the influence of menstrual cycle on HRV may be related to cyclic variations of thyroid-related hormone levels.…”
Section: Correlations Between Nonlinear and Linear Hrv Measuresmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study by Girdler et al (2004), women with premenstrual dysphoric disorder (PMDD) and a history of sexual abuse showed a greater FT3/FT4 ratio, as compared to women with PMDD and no history of sexual abuse as well as healthy controls. Friedman, Wang, Jalowiec, McHugo, and McDonagh-Coyle (2005) found significant elevations in TT3/FT4 and a significant reduction in TSH, in a community sample of 63 women with PTSD due to childhood sexual abuse as compared to 42 women without PTSD, of whom 17% also reported childhood sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, a number of studies have linked traumatic experiences to greater odds of MRMD (Perkonigg et al, 2004; Pilver et al, 2011; Bertone-Johnson et al, 2014). Moreover, those with MRMD and histories of abuse show unique alterations in various stress-responsive physiological systems that are not seen in women without a MRMD who have similar abuse histories, including the hypothalamic-pituitary-thyroid axis (Girdler et al, 2004; Bunevicius et al, 2012) and the sympathetic nervous system (Girdler, 2003; Girdler et al, 2007). Finally, we recently found that cyclical increases in P4 were associated with greater susceptibility to mood symptoms and interpersonal problems only among women high in borderline personality features (Eisenlohr-Moul et al., 2015), traits which often develop as adaptations to abuse (Bandelow et al, 2005).…”
Section: Introductionmentioning
confidence: 99%